2018
DOI: 10.1017/s1751731117001562
|View full text |Cite
|
Sign up to set email alerts
|

Analyses of reaction norms reveal new chromosome regions associated with tick resistance in cattle

Abstract: Despite single nucleotide polymorphism (SNP) availability and frequent cost reduction has allowed genome-wide association studies even in complex traits as tick resistance, the use of this information source in SNP by environment interaction context is unknown for many economically important traits in cattle. We aimed at identifying putative genomic regions explaining differences in tick resistance in Hereford and Braford cattle under SNP by environment point of view as well as to identify candidate genes deri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
14
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 53 publications
1
14
0
Order By: Relevance
“…Higher dispersion of SNP marker effects was observed when EC level became less restrictive, and the highest percentage of the genetic variance explained by an SNP was 1.029% for SC and 1.04% for HP. Mota et al (2017) observed the same trend using RNM, i.e. the range and variance of the SNP effects increased with the EC level.…”
Section: G9e Interactionssupporting
confidence: 60%
“…Higher dispersion of SNP marker effects was observed when EC level became less restrictive, and the highest percentage of the genetic variance explained by an SNP was 1.029% for SC and 1.04% for HP. Mota et al (2017) observed the same trend using RNM, i.e. the range and variance of the SNP effects increased with the EC level.…”
Section: G9e Interactionssupporting
confidence: 60%
“…Including genomic regions having environment-dependent sensitivity in statistical methods represents an additional biological insight to obtain more accurate genomic predictions and thus select Nellore heifers with greater genetic potential for sexual precocity and tolerance to harsh conditions. Streit et al 11 , in dairy cattle, and Mota et al 10 , in beef cattle,…”
Section: Resultsmentioning
confidence: 99%
“…Integrating genotypic information with reaction norm (RN) models lead to the evaluation of GxE interaction more accurately compared to only pedigree-based analysis 3,8,9 . In addition, RN models can be combined with genome-wide association studies (GWAS) allowing to uncover genomic regions involved in animal adaptation by estimating SNP effects across environmental conditions 8,10 . In this context, a greater understanding can be obtained on how genetic variants are associated with reproductive traits and the environmental sensitivity by physiological adaptation.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Another point to be highlighted is that different genes could be pronounced as potential candidates depending upon the environmental gradient, which may suggest a SNP by environment interaction affecting AFC. In a recently paper, Mota et al (2017) reported the presence of SNP by environment interactions for tick resistance in cattle affecting different tick burden levels. Therefore, models that incorporate the genotype by environment interaction should be performed.…”
Section: Discussionmentioning
confidence: 99%